2020
DOI: 10.1002/jsp2.1078
|View full text |Cite
|
Sign up to set email alerts
|

Load‐transfer in the human vertebral body following lumbar total disc arthroplasty: Effects of implant size and stiffness in axial compression and forward flexion

Abstract: Adverse clinical outcomes for total disc arthroplasty (TDA), including subsidence, heterotopic ossification, and adjacent‐level vertebral fracture, suggest problems with the underlying biomechanics. To gain insight, we investigated the role of size and stiffness of TDA implants on load‐transfer within a vertebral body. Uniquely, we accounted for the realistic multi‐scale geometric features of the trabecular micro‐architecture and cortical shell. Using voxel‐based finite element analysis derived from a micro‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…With respect to the biomechanical specifications, based on our study, the implant should meet the following requirements: Adapts the equations of the movement of the intact ICR of the joint to the post-surgical ICR [3 , 88] Behaves as a shock absorbing mechanism [58] Allows the load absorption within the implant so that adjacent levels do not overload [11] Biocompatible [37] Low implant wear [104] Different sizes to adapt to different patient geometries [59] Non-complex geometry in order to be readily manufactured [90] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the biomechanical specifications, based on our study, the implant should meet the following requirements: Adapts the equations of the movement of the intact ICR of the joint to the post-surgical ICR [3 , 88] Behaves as a shock absorbing mechanism [58] Allows the load absorption within the implant so that adjacent levels do not overload [11] Biocompatible [37] Low implant wear [104] Different sizes to adapt to different patient geometries [59] Non-complex geometry in order to be readily manufactured [90] …”
Section: Discussionmentioning
confidence: 99%
“…At the ends of this bar 10 Kg weights were hung, in such a way that a flector moment of ±25.5Nm, as well as a 0 to 100 N compression was able to be applied. This simulated physiological loading conditions [11 , 97 , 118] . The superior portion of the system was free, in order to allow greater mobility.…”
Section: Methodsmentioning
confidence: 99%
“…Footplates were assigned material properties similar to cobalt-chromium (E ¼ 210 GPa, n ¼ 0.33 36 ). Elliptical plates were chosen to represent generic footplates, thereby assuming that subtle details of implant geometry have a secondary effect on tissue-level stress relative to footplate size 19 (see Sensitivity Study, Supplemental Digital Content 1, http:// links.lww.com/BRS/B750).…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Previously, we used micro-computed tomography-(micro-CT-) based finite element analysis to study the bone biomechanics of a TDA-implanted vertebra. 19 A key advantage of this methodology is the high spatial resolution at which the bone is modeled: micro-CT-based models intrinsically incorporate the complete morphology of the calcified bone tissue, including the structural anisotropy and connectivity of the trabecular microstructure. Our prior results indicated that implant impingement induced by sagittal bending-more so than axial compression-generated high levels of bone-tissue stress, possibly increasing subsidence risk.…”
mentioning
confidence: 99%
“…Although FE models are able to deal with stresses, deformations and complex material behavior, they require a high computational time [22]. The study of Bonnheim et all [23] included a CT-based FE analysis of a vertebral body implanted with prosthetic disc implants of various sizes and stiffness. The model was loaded with compression-and flexion-induced anterior impingement.…”
Section: Introductionmentioning
confidence: 99%